2020
DOI: 10.3389/fmicb.2020.01464
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Three 22-Membered Macrolides by Deciphering the Streamlined Genome of Mangrove-Derived Streptomyces sp. HM190

Abstract: Discovery of Three 22-Membered Macrolides by Deciphering the Streamlined Genome of Mangrove-Derived Streptomyces sp. HM190.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…These metabolites were all C-4 epimers based on the julichrome Q 10 184 skeleton. 59 Analysis of various Streptomyces ferments afforded chlorinated 3-phenylpropanoic acid derivatives 188–190 , 60 MMP-1 secretion inhibitor sarmentosamide 191 , 61 a new anti-MRSA tetracene derivative, mersaquinone 192 , 62 hexacyclic xanthone ukixanthomycin A 193 , 63 butenolide mycenolide A 194 , 64 22-membered macrolides 195–197 , 65 angucycline derivatives, monacyclinones G–K 198–202 and ent -gephyromycin A 203 (ref. 66) and chromomycin A9 204 , which showed potent activity towards several microbial strains.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…These metabolites were all C-4 epimers based on the julichrome Q 10 184 skeleton. 59 Analysis of various Streptomyces ferments afforded chlorinated 3-phenylpropanoic acid derivatives 188–190 , 60 MMP-1 secretion inhibitor sarmentosamide 191 , 61 a new anti-MRSA tetracene derivative, mersaquinone 192 , 62 hexacyclic xanthone ukixanthomycin A 193 , 63 butenolide mycenolide A 194 , 64 22-membered macrolides 195–197 , 65 angucycline derivatives, monacyclinones G–K 198–202 and ent -gephyromycin A 203 (ref. 66) and chromomycin A9 204 , which showed potent activity towards several microbial strains.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…They found that PKS genes S1-S8 were proposed to be responsible for the production of three 22-membered macrolides. A total of 30 biosynthetic gene clusters (BGCs), especially gene cluster 5, were responsible for biosynthesis of the macrolide in a strain-specific 126,331bp genomic island belonging to the left-arm region [36].…”
Section: Biosynthesis Challengesmentioning
confidence: 99%
“…Interestingly, metabolomics and genomics approaches have proven to be efficient and promising tools for defining phenotypes in a dynamic context, with the potential to reduce rediscovery rates (Khoomrung et al, 2017 ; Pye et al, 2017 ; van Der Hooft et al, 2020 ), and several tools have been designed for this purpose, as reported by Caesar et al ( 2021 ). These approaches have been successfully applied to study the chemical diversity of marine bacteria and to uncover novel bioactive molecules (Macintyre et al, 2014 ; Schneider et al, 2018 ; Ye et al, 2020 ), despite the challenges encountered due to the complexity of biological matrices (Liu and Locasale, 2017 ). More recently, molecular networking, a tandem mass spectrometry (MS/MS) data organizational approach, has been introduced in the field of drug discovery (Wang et al, 2016 ), and the combination of system analyses involving multi-omics data and genome-scale, metabolic network models has greatly contributed to exploring bioactive Actinobacteria (Palazzotto et al, 2019 ) and has great potential to accelerate natural product discovery.…”
Section: Introductionmentioning
confidence: 99%